TÜRKİYE VE DANİMARKA ORTAOKUL ÖĞRETİM PROGRAMLARININ İÇERİK AÇISINDAN KARŞILAŞTIRILMASI: FİZİK KONULARI ÖRNEĞİ. - YILMAZLAR, Mustafa; ÇINAR, Sevil (Electronic Turkish Studies)
With this study, It's aimed to compare the physics lesson's content between Turkish and Danish secondary education systems in the science teaching programs. Literature review is applied in this research. The descriptive approach is used in this study which is accepted as a comparative teaching technic. In this study, it's comperatively examined the two countries' education policies, creating the carrier consciousness, physics lesson's which takes part in teaching programs, aims and benefits of physics lessons, interdiscipliner approach, distribution of learning parts and units according to class level, lesson's duration of physics and international PISA examination's results. And also it's tried to make it clear the similarities and diffirencies with this study. Interdiscipliner approach has more importance in Denmark than Turkey according to results. Lessons duration which is allocated for Physic lessons is close to each other in this two countries. However it's recognized that benefits of physisc lessons in Denmark is more little than Turkey. It's trying to establish phyics carrier in the early ages in Denmark, different from Turkey and also there are research opportunity at the universities for secondary school students in Denmark. According to international exam results, Danish students records are higher than Turkish counterparts. There is a few related studies about the analyzing the Danish teaching programs. But there is no research about the comparison between Danish and Turkish physics lesson's according to literature review. So it's recommended that it should be examined by the help of more similar studies about both science teaching lessons and other lessons for the different education levels.